A mathematical model for estimating the return on the exploitation of natural capital based on contemporary economic ideas - Taha, Ayad; Najeeb , Shaima (Humanities Journal of University of Zakho, 2021)
Natural capital reflects the stock of renewable, non-renewable resources and includes (vegetation, wild animals, air, water, soil, minerals ... etc.) that result from the flow of benefits to members of society, as it includes a wide range of environmental services and goods provided by Natural capital, food and water, energy, shelter, medicine, and raw materials. The basic idea of ​​the research starts by linking the ideas of the economist (Luigi Pasinetti i), who finds in his model that saving depends on the reward of profits, and that the savings that come from the savings of the procedure is what is deduction from the ratio of saving to reward the profits, as the capitalists ’profits turn into savings and an investment that leads to a capital accumulation Money, but the main idea of ​​this research comes from the(Robert M. Solow ) analysis, which states that the (Cobb–Douglas ) formula, which includes work and capital, as capital is divided into two types, which are physical capital, and natural capital, and from this idea is based on that part of the capital Money comes from nature , Which could drain on non-renewable natural resources and relies on renewable natural resources, and here began research in an attempt to link the two ideas and to provide a model mathematically a proposal to determine the yield derived from natural capital.